MICROBIOLOGICAL PROFILE FROM MIDDLE EAR AND NASOPHARYNX IN PATIENTS SUFFERING FROM CHRONIC ACTIVE MUCOSAL OTITIS MEDIA - Khattak, Shahid Farooq; Sheikh, Nadeem Ahmed; Aleem, Adil (Journal of Ayub Medical College Abbottabad, 2017)
Background: Chronic otitis media is described as a tympanic membrane perforation and ear discharge for more than six weeks duration. Ascending infection from the nasopharynx into the middle ear cleft has been attributed to prevent resolution of chronic otitis media. This research aims to determine the association between the microbiological flora of the nasopharynx with that of the middle ear in patients suffering from chronic (active) mucosal otitis media. Methods: Our study is a hospital-based cross-sectional survey. It was conducted from December 2015 to February 2017 at the Department of ENT, Combined Military Hospital, Abbottabad. Ear and nasopharyngeal swabs were obtained from 65 patients of chronic active mucosal otitis media and sent for microbiological analysis. Microbiological culture and sensitivity test was performed to identify the microbial spectrum of each specimen. Performa bearing the result of otoscopy, aspirate and swabs were completed for middle ear and the nasopharyngeal culture with reference to each patient. Descriptive statistics and Pearson's chi square analysis were performed using SPSS-22. Results: Staphylococcus aureus and Pseudomonas aeruginosa are foremost micro-organisms found in otorrhea culture isolated from patients of chronic active mucosal otitis media. Majority of the cultures from nasopharynx of these patients did not reveal any growth after incubation for 48 hours. Conclusion: A statistically insignificant association exists between the microbiological spectrum of the middle ear and the nasopharynx of patients suffering from chronic active mucosal otitis media. Micro organisms' exposure from a perforated tympanic membrane remains leading cause of persistent otorrhea, rather than ascending infection through the Eustachian tube. Key words: Otitis, otitis media; suppurative; culture techniques; microbiology